Exercise time cues (zeitgebers) for human circadian systems can foster health and improve performance: a systematic review. Issue 1 (5th December 2018) - Lewis, Philip; Korf, Horst W; Kuffer, Liz; Groß, J Valérie; Erren, Thomas C
Abstract : Background: Circadian system time cues (zeitgebers) acting synergistically at the right times can foster chronobiological homeostasis and ultimately health. Modern 24/7 societies are challenging chronobiological homeostasis and public health. Exercise has been discussed as a potential zeitgeber for the human circadian system. Thus, if timed correctly, exercise may help in maintenance of chronobiological homeostasis and foster public health amidst increasingly challenging 24/7 lifestyles. Objective: To test, using a systematic review of the literature, the following hypothesis: exercise is a zeitgeber for the human circadian system. Data sources: The PubMed database was systematically searched on 19 October 2017 for relevant scientific studies and reports concerning chronobiology and exercise. Eligibility criteria were defined to include articles considering exercise as a potential zeitgeber for human circadian rhythmicity or chronobiological effects of exercise on health and/or physical performance. Cognitive effects and effects on children were excluded from the synthesis. Results: Our systematic literature search and synthesis is compatible with the validity of the hypothesis. We report that potential exercise-zeitgeber properties may be used to improve health and performance. Conclusions: Informed timing of exercise, specific to the circadian rhythm phase and zeitgeber exposure of the individual, must be advocated in performance and disease contexts as an adjunct therapeutic or preventative strategy and physical enhancer.